Pengaruh Corporate Social Responsibility dan Mekanisme Good Corporate Governance Terhadap Kinerja Perusahaan - Dhistianti Mei Rachmawantari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to examine the effect of Corporate Social Responsibility and Good Corporate Governance on Company Performance in Food and Beverage Manufacturing Companies Listed on the IDX for the 2019-2022 period. The data used in this research is quantitative data. The sampling technique using purposive sampling obtained a total sample of 48 data. The results of the study show that Corporate Social Responsibility (CSR) influences company performance. Good Corporate Governance (GCG) has no effect on company performance. Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) have an influence on company performance.